Customer Lifetime Model for the Magazine Publishing Industry - Basu, Kallol (Indian Journal of Marketing, 2010)
Since ages, magazines have served the information requirements of readers around the globe. However with the global economic slowdown, magazine publishers are forced to not just supply information, but also analyze ways to serve its clientele better. In this paper, we try to understand the potential trends and phases that magazine publishing lifecycle typically encounters. Thereafter, we try to simulate a model that can calculate the customer lifetime value for magazine publishers which would also aid in understanding the implications of the same.